Oral Presentation Versus Role Playing in Medical Education: A Quasi-Experimental Study - Majid Khadem-Rezaiyan; Malihe Dadgar Moghadam (Kerman University of Medical Sciences, 2018)
Background It is claimed that role-playing is a teaching strategy that has several advantages for both the teacher and student. This study aimed to compare two educational methods (oral presentation, a traditional method that is known to be teacher-centered, versus role-playing which is a student-centered method). Methods This quasi-experimental study was performed between September 2013 and October 2014 in 95 medical students in Mashhad University of Medical Sciences. Role-playing and oral (plus Microsoft PowerPoint) presentation were done by one assistant professor. There were no changes in the educational content nor the classroom. Using random numbers, half of each group received one of the methods as the first class and vice versa. At the end of each session, the standard satisfaction evaluating questionnaire was filled by the students. Results During the one-year duration of this study, 95 students were evaluated, and 46 (60%) of them were female. The mean age was 22.5 ± 1 years, and 28 (87.5%) were single. Role-playing had a mean rank of 54.64, and oral presentation had 21.45 (P < 0.001). This difference was present based on gender as well (P < 0.001). The satisfaction score was significantly higher for role-playing (P < 0.001). Conclusions Role-playing can be much more helpful in education and needs to be incorporated into the lesson plans.